Analysis and Design of Incoming and Outgoing Cash Accounting Information Systems at Kilometer 28 Laundry using the Pieces and Waterfall Methods with Unified Modeling Language (Uml) Tools - Indah Nurlita; Reni Anggraini (Formosa Journal of Applied Sciences, 2023)
This research focuses on helping Laundry Kilometer 28 in recording cash in and cash out transactions which are still manual so it is not efficient because of the increase in customers. Researchers conducted an analysis using the PIECES method to find out how the system is running, what are the system deficiencies and what the system needs. The researcher designed a system for recording incoming and outgoing cash at Laundry Kilometer 28 using the waterfall method with UML (Unified Modeling Language) tools. Methods of data collection in the form of interviews and direct observation to analyze the Kilometer 28 Laundry business process to owners, cashiers and regular customers. The results of this study are system design with use case diagrams, activity diagrams, class diagrams and sequence diagrams compiled with draw.io, Microsoft Visio Drawing which is then visualized for its interface with Microsoft Power Point.